Efeito do estresse precoce sobre citocinas no cérebro : uma revisão sistemática e meta-análise de estudos com roedores - Lumertz, Francisco Sidermann (2022)
Introduction: Exposure to early life stress (ELS) is a risk factor for adverse outcomes in relation to cognition, behavior, neurodevelopment and psychiatric disorders. It is hypothesized that the activation of neuroinflammatory signaling is one of the possible mechanisms associated with damage resulting from exposure to ELS. Objective: To conduct a systematic review and mata-analysis on the effects of ELS on inflammatory cytokines in the rodent brain. Methodology: A systematic review was performed in PubMed, Web of Scince and PsycInfo, and meta-analysis to identify the effect of ELS on the expression of inflammatory cytokines in the rodent brain. An assessment of the methodological quality of the studies was performed, as well as a meta-regression on the metaanalytic data to investigate possible moderators for the heterogeneity of the results obtained. Results: Thirty one studies were included. The meta-analysis showed that the levels of the pro-inflammatory cytokines IL-1β, IL-6, and TNF-α were elevated in animals exposed to ELS compared to control animals, but it was not possible to observe differences in the levels of IL-10. Meta-regression showed that the effects of ELS were greater in the hippocampus, that longer periods of stress resulted in more lasting effects, protein expression was primarily affected by stress, undergoing events such as behavioral testing increased the effect of ELS, and that older animals had a stress desensitization effect. Conclusion: Exposure to ELS might alter the expression of inflammatory cytokines in the brain of rodents, especially the cytokines IL-1β, IL-6 and TNF-α, with a larger effect size in the hippocampus and as a consequence of at least eight days of exposure to ELS. Although ELS has an effect on neuroinflammatory changes, this effect may not last until senescence, suggesting that secondary exposure to stressful situations is necessary to cause more robust and long-term effects.